2019
DOI: 10.1051/0004-6361/201936322
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the near-infrared extinction curve towards the Galactic centre

Abstract: Context. Due to the extreme extinction towards the Galactic centre (A V ∼ 30 mag), its stellar population is mainly studied in the near-infrared (NIR) regime. Therefore, a proper analysis of the NIR extinction curve is necessary to fully characterise the stellar structure and population of the inner part of the galaxy. Aims. We studied the dependence of the extinction index (α λ ) in the NIR on the line of sight, wavelength, and extinction. Methods. We used the GALACTICNUCLEUS imaging survey, a high angular re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 37 publications
5
53
0
Order By: Relevance
“…All the parameters that we obtain in the fits are consistent with the final results in Table 2 at the 3σ level. We repeat the procedure to study the effect on the final NSC parameters of the extinction index uncertainty from Nogueras-Lara et al (2018b, 2019c) ( α = 0.08). We use α = 2.38 and α = 2.22, respectively.…”
Section: Appendix A1: Extinction and Completenessmentioning
confidence: 99%
“…All the parameters that we obtain in the fits are consistent with the final results in Table 2 at the 3σ level. We repeat the procedure to study the effect on the final NSC parameters of the extinction index uncertainty from Nogueras-Lara et al (2018b, 2019c) ( α = 0.08). We use α = 2.38 and α = 2.22, respectively.…”
Section: Appendix A1: Extinction and Completenessmentioning
confidence: 99%
“…Nevertheless, recent studies have found some evidence of a wavelength-dependence of the extinction index (Nogueras-Lara et al 2018a;Hosek et al 2018). In particular, Nogueras-Lara et al (2019b) analysed the extinction law in the NIR towards the central region of the NSD and found that the extinction index depends on wavelength, but not on the line-ofsight. This dependence has strong implications on the derivation A&A 641, A141 (2020) Fig.…”
Section: Introductionmentioning
confidence: 99%
“…of the structure of the innermost part of the Galaxy and the identification of the stellar type via NIR photometry, since a small change in the extinction index (∼10−15%) leads to a significant change in absolute extinction (∼0.3 mag, e.g. Matsunaga et al 2016;Nogueras-Lara et al 2019b) that might be translated into a biased estimation of the distance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme and spatially highly variable interstellar extinction toward the GC (Nishiyama et al 2008;Fritz et al 2011;Nogueras-Lara et al 2019b) makes it practically impossible to identify young clusters in the near-infrared (NIR) colour-magnitude diagrams (CMDs), which are almost fully degenerate because of reddening (Nogueras-Lara et al 2018). However, stellar proper motions can provide us with an alternative way of detecting young clusters, which are expected to show coherent proper motions.…”
Section: Introductionmentioning
confidence: 99%